PEREMPUAN DALAM STRUKTUR SOSIAL BUDAYA ORANG KAILI DI SULAWESI TENGAH: (Suatu Tinjauan Antropologi Feminis) - Citra Dewi (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
This essay is a form of 'diversity' of views in contemporary feminist ethnography which views that women are not a single category (that all women suffer from the same oppression). This research is intended to frame the community's cultural values ??related to the position of women and see their relationship with the socio-cultural structure of the Kaili people. The question being asked is what is the position or position of women in the socio-cultural structure of the Kaili people? The results of the study show that women in the life of the Kaili people are placed in a central position. This is reflected in the cognitive structure of the Kaili people through the Tomanuru myth. Tomanuru is described as a wise, fair, honest and cooperative woman. who was deliberately sent down to earth to accompany Tomalanggai, who later became known as the ancestors of the Kaili people. Meanwhile, at a practical level, the roles played by women within the scope of the nuclear family (koyompuse) are embodied in the role of bulonggo who has the power to control the family's economic resources. Within the scope of the extended family (Santina), the role of women is reflected in the concept of tina, including tina numbara-mbara, tina nurombe. Meanwhile in the wider community (savalantambako), tina nubalia and tina ngata emphasize the presence of women as leaders and even as main figures in the embodiment of a ritual and the benefit of the village. The central roles of these women are a form of recognition of women's abilities and equality.